The efficacy of the dopamine agonist Rotigotine in the treatment of Parkinson's disease - Marina Romanovna Nodel (Неврология, нейропсихиатрия, психосоматика, 2013)
Rotigotine is a new, non-ergot dopamine receptor agonist (DRA) formulated as a transdermal drug delivery system. This article reviews the clinical efficacy and tolerability of Rotigotine transdermal patch in Parkinson's disease (PD) and discusses the results of clinical trials of Rotigotine in early- and late-stage PD. The Rotigotine transdermal patch is efficacious in the treatment of PD. Drug-related adverse events (AEs) include side effects typical for DRA, which are generally mild or moderate in intensity. The most common AEs are local reactions that are mild or moderate. Once-daily administration of the rotigotine transdermal patch is effective in the treatment of patients with early-stage PD as monotherapy and in combination with levodopa in late-stage PD and in inadequate morning motor control despite antiparkinsonian treatment.